DNA Methyltransferases Contribute to Cold Tolerance in Ticks Dermacentor silvarum and Haemaphysalis longicornis (Acari: Ixodidae) - Agwunobi, Desmond Onyeka; Zhang, Miao; Shi, Xinyue; Zhang, Shiqi; Zhang, Meng; Wang, Tongxuan; Masoudi, Abolfazl; Yu, Zhijun; Liu, Jingze (Frontiers in Veterinary Science, 2021)
DNA methylation, mediated by DNA methyltransferases (Dnmts), is a typical epigenetic process that plays an important role in affecting organism acclimatization and adaptation to environmental changes. However, information about Dnmts and their associations with the cold tolerance of ticks remains meager. Hence, in the present study, the Dnmts in important vector ticks Dermacentor silvarum and Haemaphysalis longicornis were cloned and identified, and their functions in cold response were further explored. Results showed that the length of DsDnmt and DsDnmt1 in D. silvarum, and HlDnmt1 and HlDnmt in H. longicornis were 1284bp, 549bp, 1500bp, and 1613bp, respectively. Bioinformatics in protein analysis revealed that they were all unstable hydrophilic proteins and were mainly characterized with Dcm (DNA cytosine methyltransferase domain), Dnmt1-RFD (DNA methyltransferase replication foci domain), zf-CXXC (zinc finger-CXXC domain), and BAH (Bromo adjacent homology domain). The relative expression of these Dnmts was reduced after cold treatment for 3 days (P < 0.05), and increased with the extension of treatment. Western blot revealed that Dnmt1 decreased first and then increased significantly (P < 0.05) in both tick species, whereas other Dnmts fluctuated at varying degrees. RNA interference significantly silenced the genes Dnmts (P < 0.01), and mortality increased significantly (P < 0.05), when exposed to sub-lethal temperature, underscoring the important roles of Dnmts during the cold response of D. silvarum and H. longicornis. The above results lay the foundation for further understanding of the epigenetic regulation of DNA methylation in cold acclimatization and adaptation of ticks.